Intertextuality, Its Structure And Aesthetics An Applied Study On The Novel “tamasakht” By Al-habib Al-sayeh - ammar, mahdi (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
The term "intertextuality" appeared in the field of Arab critical studies relatively late compared to its appearance in Western criticism, where Arab criticism received it in a way that contained a lot of confusion and confusion due to its association with concepts related to: comparative literature, acculturation, and literary theft..., However, its meaning to modern Arab researchers is almost the same as that of Westerners. However, it faced the problem of the multiplicity of the term, similar to many Western critical terms transferred to Arabic criticism, and this is what made the student find it difficult to find a single verbal formulation for it, so there were many translations and names. Among them: (intertextuality, textuality, intertextuality...), and despite this, it dominated the field of Arab critical studies, and took up the largest space in it.